Maḥmūd Yūnus wa Ittijāhātuhu fī Tahdīd Ta‘līm al-lughah al-‘Arabīyah bi Indūnīsīyā - Syafruddin, Didin (Studia Islamika, 1995)
Mahmud Yunus is one of the Indonesian students who was in Cairo in the thirties and is seen to have made a great contribution to the development of national Islamic education since the time of Indonesian independence. Having finished his studies at al-Azhar University 1927, Yunus studies at Darul Ulum to widden his intellectual horizon untul he obtained his certificate in 1930. As a graduate of one of the most important centers of Islamic learning, he had a lofty status in the Muslim community. Yunus served as a teacher in an Islamic teacher training school (Normal Islam), in padang, West Sumatra and later he was appointeed as a goverment official, seeking to establish and improve Islamic school in Indonesia. He was also a rector and professor of Islamic education at the State Institute of Islamic Studies in Padang.DOI: 10.15408/sdi.v2i3.831